Peran Perempuan dalam Menanggulangi Kemiskinan di Indonesia Tahun 2017-2021 - Zahra, Patimah; Usman, Hardius (Jurnal Dinamika Ekonomi Pembangunan, 2024)
Indonesia is still grappling with poverty issues, both at the national and regional levels. The trend shows a downward movement, although the pace of decline tends to be slow and has not been able to meet the poverty target set forth in the RPJMN 2020-2024. Thus, there is a need for innovation in poverty alleviation policies. One such approach is maximizing the role of women. When women participate in productive economic activities, the welfare of their families increases, which can reduce the poverty rate in aggregate. Therefore, this study aims to analyze the influence of variables representing the role of women on poverty levels in Indonesia from 2017 to 2021. The method used is panel data regression with the FEM selected model and the FGLS-SUR estimation method. The results show that women’s pure participation rate, women's life expectancy, the percentage of households with female heads, women's adjusted per capita expenditure, women's average wages, and women's labor force participation rate have a negative and significant effect on poverty levels, while women's open unemployment rate has a positive and significant effect on poverty levels. Meanwhile, women's literacy rate has a negative but insignificant effect on poverty levels.